PERAN KEPALA MADRASAH DALAM MEWUJUDKAN BUDAYA KERJA YANG HANDAL - ABDULLAH K (Adaara: Jurnal Manajemen Pendidikan Islam, 2018)
Abstract. Work culture is part of the view that makes values, habits, strengths and drivers in the life of the group organization, which reflects patterns of attitudes, behavior and beliefs, ideals, opinions and actions in the work. Work culture is one of the components of human quality that is deeply embedded in national identity and is a basic benchmark in development. It was hoped that the head of the madrasah would be able to influence and mobilize the individual spirit in his institution in the form of solid cooperation in realizing a reliable work culture. A reliable work culture will have a positive impact on institutional management, such as respecting time, working as well as possible and professionally, working honestly and being of worship value, increasing work performance, building management of openness and healthy competition, eliminating collusion of nepotism and corruption, building employment opportunities together with all subordinates in developing achievements, careers and positions and applying efficient and effective ways of working. Kata kunci: Head of madrasa and a reliable work culture.